ANALYSIS OF RESIDENTIAL FECAL SLUDGE LOADING FACTOR FROM SEPTIC TANK IN BANDUNG CITY - Afina Hasibuan, Munira
Pollutant load or emission factor from domestic wastewater is a serious environmental issue that should be evaluated. According to the Ministry of Environment and Forestry, 2017, the largest contributor to BOD pollutant in Citarum watershed comes from domestic wastewater (62.16%), and the biggest contributor to BOD pollutant in Bandung City is also domestic waste (94.15%). It is necessary to plan an effective domestic wastewater treatment system as an effort to prevent contamination to the environment, thus per capita pollutant loading factor of Bandung City is needed. Seeing that the most widely used domestic wastewater treatment in Bandung City is On-site Sanitation System (OSS) (38.47%), and the type of OSS most commonly used is septic tank, this study was conducted to determine the load factor of fecal sludge from residential area in Bandung City. TSS, COD, BOD, and Ammonia were tested from 30 samples of fecal sludge. Based on the results of the study, the range of fecal sludge pollutant load factor in Bandung City is 57.28 g/person/day – 1,064 g/person/day with an average of 546.39 g/person/day, the range for total COD is 30.06 g /person/day – 294.99 g/person/day with an average of 294.99 g/person/day, the range for total BOD is is 14.05 g/person/day – 504.97 g/person/day with an average of 175.5 g/person/day, and the range for ammonia is 1.61 g/person/day – 3.11 g/person/day with an average of 2.62 g/person/day. The results from this study are expected to be used as a base data in preparation of designing domestic sewage treatment infrastructure, as well as improvement of domestic sewage treatment systems. Additionally, the pollution load factor is also expected to be used in the calculation of potential polluters, preparation of city spatial planning and in the study of Water Pollution Control (WPC) policies